Diagnosis and treatment of infraspinatus tendon-bursa ossification in a Eurasian Dog - Ungru, Julia; Hungerbühler, Stephan; Henninger, Wolfgang; Klupiec, Petra; Bödeker, Julia; Langer, Anna; Fehr, Michael; Harms, Oliver (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
A 4-year-old male Eurasian Dog presented at our veterinary clinic with a history of perpetual forelimb lameness in both thoracic limbs. In the clinical exploration, direct pressure over the infraspinatus tendon of insertion caused pain in both thoracic forelimbs and a firm band-like structure was palpable. No improvement was observed after treatment with rest, non-steroidal anti-inflammatory drugs and an intralesional injection of a long-acting glucocorticoid. Radiographic examination, ultrasonographic exploration and computed tomography were performed, identifying ossified structures lateral to the proximal humerus and an irregular roughened periosteum at the insertion and tendon of the infraspinatus muscle on both sides. There were more distinct alterations on the right thoracic limb. The imaging results led to a diagnosis of an infraspinatus tendon-bursa ossification accompanied by a chronic tendinopathy/tendovaginitis, accentuated on the right side. The dog was subjected to physiotherapy and autologous conditioned plasma (ACP) was injected into the insertion of the infraspinatus muscle of both thoracic limbs. After 5 months of physiotherapy and two injections of ACP with an interval of one week in both forelimbs, the dog showed no signs of lameness. This case report describes the diagnosis and management of infraspinatus tendon-bursa ossification in a Eurasian Dog. To the authors’ knowledge, this condition has previously not been described in this breed of dog.
Keywords: Forelimb lameness; shoulder joint; ossified structures; physiotherapy; autologous conditioned plasma